2016
DOI: 10.1063/1.4962132
|View full text |Cite
|
Sign up to set email alerts
|

Edge structures and properties of triangular antidots in single-layer MoS2

Abstract: Density functional theory and experiments are employed to shed light on the edge structures of antidots in O etched single-layer MoS2. The equilibrium morphology is found to be the zigzag Mo edge with each Mo atom bonded to two O atoms, in a wide range of O chemical potentials. Scanning electron microscopy shows that the orientation of the created triangular antidots is opposite to the triangular shape of the single-layer MoS2 samples, in agreement with the theoretical predictions. Furthermore, edges induced b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…Interestingly, we found that these bright edge regions of the α domain are populated with a number of triangular holes with sizes of 25–2500 nm 2 (Figure b). We believe that these holes are a result of gradual oxidative etching by absorbed water and oxygen molecules . It is noteworthy that no such damage is found in the β domains.…”
Section: Discussionmentioning
confidence: 80%
“…Interestingly, we found that these bright edge regions of the α domain are populated with a number of triangular holes with sizes of 25–2500 nm 2 (Figure b). We believe that these holes are a result of gradual oxidative etching by absorbed water and oxygen molecules . It is noteworthy that no such damage is found in the β domains.…”
Section: Discussionmentioning
confidence: 80%
“…When heated in the presence of oxygen, the reaction forms MoO 3 and SO 2 molecules: MoS 2(s) + 3.5O 2(g) → MoO 3(s/g) + 2SO 2(g) (1) The temperature at which the reaction occurs is greatly determined by the condition of the material, reportedly ranging from 100°C for a powder 20 , to 400°C 22 for sputtered MoS 2 coatings. The oxidative thinning and/or etching of 2D MoS 2 can be achieved by heating in the presence of O 2 to ∼240°C or higher [1][2][3][4]23 . Other oxidants have also been used such as the more reactive O 3 24,25 , XeF 2 26 and oxygen containing plasmas [27][28][29] .…”
Section: Introductionmentioning
confidence: 99%
“…Other oxidants have also been used such as the more reactive O 3 24,25 , XeF 2 26 and oxygen containing plasmas [27][28][29] . Many reports demonstrate a mesh of quasiequilateral triangular pits in the MoS 2 surface after exposure to oxidizing conditions [1][2][3]23 . These pits are likely bounded by the p-doped zig-zag-Mo edge, with each Mo atom bonded to two O atoms in a wide range of O chemical potentials 2,23,30,31 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the size of antidots is increased, creating a RTA lattice becomes slightly more energetically favorable than creating an ETA lattice, while the energy gaps in ETA structures are slightly larger than those in RTA structures. Interestingly, the linear reduction of formation energy by increasing the size of similar ETA lattices but passivated by oxygen atoms has also been reported in single-layer MoS 2 antidots using DFT calculations combined with experiments 38 . Moreover, it is suggested that since the formation energy of all antidot sizes and shapes is negative, it is probably feasible to create them by heating the samples in air 38 .…”
Section: Resultsmentioning
confidence: 57%